The perceptions of high school teachers and students towards digital interest and literacy - Achmad, Reza Khaidar; Mulyati, Yeti (Jurnal Inovasi Teknologi Pendidikan, 2023)
The increased application of information and communication technology (ICT) in society promotes its use in education to align instructional content with students' interests and future working lives. To achieve this, the human resources within education institutions must possess the ability to utilize technology and understand the students' capabilities. This descriptive study was conducted to establish the profile of students' and teachers' interests and perceived digital literacy abilities in high schools and their equivalents. An online questionnaire was used to collect data from West Java, West Kalimantan, and Jakarta high schools. The gathered data were processed with a simple quantitative technique. The data analysis collected by the questionnaire indicates that the respondents have a relatively high perception of digital literacy levels (encompassing operational, information, communication, strategic, and creative abilities), with some relatively low aspects, such as expressing opinions and creating things with ICT. Furthermore, it was also found that respondents exhibit a strong interest in using digital devices for learning, with video games, video processing programs, and graphic design software occupying the three least used digital media in schools but most desired by the respondents for integration.